2022
DOI: 10.1200/go.22.00118
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review of Hepatocellular Carcinoma in India: Current Challenges and Future Directions

Abstract: There is not much information on hepatocellular carcinoma (HCC) in India. Here, we review the existing data, available treatment choices, and future directions in HCC management. An extensive search was conducted through PubMed and MEDLINE for studies published between January 2000 and June 2022 on the epidemiology of HCC in India using the following key words: atezolizumab, BCLC staging, hepatocellular carcinoma, immune checkpoint inhibitors, immunotherapy, and programmed cell death ligand-1, with the filters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Hepatitis B infections are at present the main risk factors for HCC. Moreover, the presence of cirrhosis, metabolic disorders, and autoimmune diseases as well as genetic predisposition are factors increasing the risk of HCC (Shetty and Kellarai, 2022). Surgical resection represents the established therapeutic approach for HCC patients with good liver function and no obvious vascular invasion or distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B infections are at present the main risk factors for HCC. Moreover, the presence of cirrhosis, metabolic disorders, and autoimmune diseases as well as genetic predisposition are factors increasing the risk of HCC (Shetty and Kellarai, 2022). Surgical resection represents the established therapeutic approach for HCC patients with good liver function and no obvious vascular invasion or distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…PLC is a heterogeneous group of diseases, including hepatocellular carcinoma, which constitutes over 90%, intrahepatic cholangiocarcinoma and combined hepatocellular cholangiocarcinoma. Various risk factors have been identified that can heighten the probability of developing PLC, including smoking, exposure to aflatoxin, hereditary hemochromatosis, infection with hepatitis B and C viruses, cirrhosis, chronic biliary diseases, choledocholithiasis, autoimmune diseases like autoimmune hepatitis, primary sclerosing cholangitis and primary biliary cholangitis, as well as metabolic disorders including diabetes and non‐alcoholic fatty liver disease 4 …”
Section: Introductionmentioning
confidence: 99%
“…Various risk factors have been identified that can heighten the probability of developing PLC, including smoking, exposure to aflatoxin, hereditary hemochromatosis, infection with hepatitis B and C viruses, cirrhosis, chronic biliary diseases, choledocholithiasis, autoimmune diseases like autoimmune hepatitis, primary sclerosing cholangitis and primary biliary cholangitis, as well as metabolic disorders including diabetes and non-alcoholic fatty liver disease. 4 In recent years, researchers have paid more attention to the impact of living habits on the incidence and development of disease. More people are facing sleep problems such as insomnia, inadequate sleep duration, obstructive sleep apnea (OSA) and daytime napping.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of liver cancer has been on the rise in recent years, and it is estimated that by 2030, it will become the second leading cause of cancer-related deaths worldwide. 1 When liver cells are damaged or destroyed due to various factors, such as chronic hepatitis B or C infections, excessive alcohol consumption, or exposure to toxins, the liver tries to repair itself by regenerating new cells. However, this process can sometimes go awry and result in the formation of cancerous cells.…”
Section: Introductionmentioning
confidence: 99%
“…3 Therefore, for successful treatment and a high patient survival rate, early detection of liver cancer is the holy grail in liver cancer study. 4 It is found that many patients with liver disease like hepatocellular carcinoma, liver fibrosis, and cirrhosis etc. exhaled mixture of specific VOCs which would have normally not present if the liver would have functioning well.…”
Section: Introductionmentioning
confidence: 99%